Lean in women, work, and the will to lead - Sandberg, Sheryl (New York Alfred A. Knopf, 2013)
Thirty years after women became 50 percent of the college graduates in the United States, men still hold the vast majority of leadership positions in government and industry. This means that women?s voices are still not heard equally in the decisions that most affect our lives. In Lean In, Sheryl Sandberg examines why women?s progress in achieving leadership roles has stalled, explains the root causes, and offers compelling, commonsense solutions that can empower women to achieve their full potential.
Includes index
Keywords: Sandberg, Sheryl